The Uses and Abuses of Footnotes - Ira, Jaroslav (Dějiny – teorie – kritika, 2016)
The aim of this contribution is to stimulate a debate and a critical reflection of the uses and abuses of footnotes and referencing apparatus in general. In the author’s view, both history students and professional historians often fail to fully appreciate the various possible functions of footnotes in the text, and more generally in academic communication and scientific community at large. Consequently, footnotes and references are often used inaccurately. Redundant and poorly considered use of footnotes often creates an illusion of scientific quality of a text while concealing its emptiness in terms of interesting or novel content. Moreover, it distorts the system of distribution of academic credits. This brief study summarises the main functions of footnotes, considers some kinds of bad practice, and fi nally argues in favour of better considered use of footnotes, which it views as an integral part of the overall argumentative structure of an academic text.